Attempts to eliminate methotrexate (MTX) by means of extra-corporeal blood purification in MTX-induced acute renal failure - Ito, Hiroo; Okada, Hiroshi; Fujisawa, Kayoko; Nagase, Mitsumasa; Chimata, Minoru; Hidaka, Sumi; Nakamura, Kazumichi; Kakuta, Sachiko (Journal of Japanese Society for Dialysis Therapy, 1991)
High-dose methotrexate (MTX) therapy has been proposed to be effective for the treatment of osteosarcoma. However, it frequently induces acute renal failure (ARF). Since the drug is excreted mainly through the kidney, MTX-induced ARF per se also contributes to the retention of MTX, thereby enhancing side effects of the drug other than ARF. Therefore, it is mandatory to attempt to eliminate MTX particularly in ARF. In our recently experienced MTX-induced ARF, direct hemoperfusion (DHP), hemodialysis (HD) and/or plasma exchange (PE) were performed singly or in combination. Better elimination rates were obtained in the order of PE, DHP+HD, DHP and HD. However, more marked decline of serum MTX was noted along with increased urine volume and decreased serum creatinine. Although it is clear that intact renal function exceeds any of the blood purification means in terms of MIX elimination, these attempts should be made to minimize the side effects particularly when renal function is impaired. Of the 3 methods we have herein applied, PE seems to be the most effective. However, PE is not recommended in view of the hazard of infection such as hepatitis virus and also from a socioeconomical perspective. DHP combined with HD, therefore, is preferable to PE. Therefore, we propose that in ARF, repetition of DHP plus HD shoud be introduced in order to minimize the side effects of MTX.